2019
DOI: 10.3390/en12183569
|View full text |Cite
|
Sign up to set email alerts
|

Day Ahead Hourly Global Horizontal Irradiance Forecasting—Application to South African Data

Abstract: Due to its variability, solar power generation poses challenges to grid energy management. In order to ensure an economic operation of a national grid, including its stability, it is important to have accurate forecasts of solar power. The current paper discusses probabilistic forecasting of twenty-four hours ahead of global horizontal irradiance (GHI) using data from the Tellerie radiometric station in South Africa for the period August 2009 to April 2010. Variables are selected using a least absolute shrinka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 39 publications
1
34
0
Order By: Relevance
“…Following the unprecedented success in the Global Energy Forecasting Competition 2014, QRA became a popular technique for probabilistic energy forecasting (see, e.g., Zhang et al, 2016;Liu et al, 2017;Zhang et al, 2018;Kostrzewski and Kostrzewska, 2019;Mpfumali et al, 2019;Serafin et al, 2019;Uniejewski et al, 2019;Wang et al, 2019). However, a recent study of Marcjasz et al (2020) has revealed the method's vulnerability to low quality predictors when the set of regressors is larger than just a few.…”
Section: The Expert Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the unprecedented success in the Global Energy Forecasting Competition 2014, QRA became a popular technique for probabilistic energy forecasting (see, e.g., Zhang et al, 2016;Liu et al, 2017;Zhang et al, 2018;Kostrzewski and Kostrzewska, 2019;Mpfumali et al, 2019;Serafin et al, 2019;Uniejewski et al, 2019;Wang et al, 2019). However, a recent study of Marcjasz et al (2020) has revealed the method's vulnerability to low quality predictors when the set of regressors is larger than just a few.…”
Section: The Expert Modelmentioning
confidence: 99%
“…Formally introduced by Nowotarski and Weron (2015), Quantile Regression Averaging (QRA) has sparked interest in the EPF community after its unprecedented success in GEFCom2014, where the top two winning teams in the price track - Gaillard et al (2016) and -used variants of QRA. Since the method is a general forecasting technique not limited to electricity prices, a number of authors have reported its successful application Email addresses: bartosz.uniejewski@pwr.edu.pl (Bartosz Uniejewski), rafal.weron@pwr.edu.pl (Rafał Weron) in areas ranging from load (Liu et al, 2017;Zhang et al, 2018;Wang et al, 2019) to wind power (Zhang et al, 2016) and irradiance forecasting (Mpfumali et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Solar radiation is a primary factor affecting power output. Some studies are ongoing with the goal of estimating solar radiation to predict future power output [30][31][32]. There are also studies on power output estimation based on ambient temperature, wind velocity, and incident light [33][34][35].…”
Section: Solar Power Estimation and Inverter Efficiency Analysismentioning
confidence: 99%
“…The obtained results showed a very high accuracy. Besides, in South Africa [34], a research study carried out for discussing probabilistic of forecasting the GHI before 24 hours, using two machine learning methods and the data collected during the period from 2009 to 2010. The study gave excellent results but not exceeded by 95.5%.…”
Section: Literature Reviewmentioning
confidence: 99%